Research on small ruminant production systems in Zimbabwe - Ndlovu, L.R. (1993)
In 1980, very little was known about any aspect of communal area small ruminant production and productivity, even though small ruminants were an integral component of communal area farming systems. The Departement of Animal Science, in line with the government policy of prioritizing communal area agriculture, embarked on a research programme to study the existing production levels of communal area small ruminants. This information was to be used to design appropriate technologies for interventions to improve this production. A grant was obtained from an external donor to carry out the research programme. The research was carried out with the assistance of Research fellows registered for higher degree. In this way the project enhanced the development of human resources. The programme consisted of both on-station and on-farm research. On-station work emphasized biological components of small ruminant production whilst on-farm work mainly consisted of monitoring studies with minor interventions such as the introduction of new forage species and multipurpose trees. On-station work showed that indigenous small ruminants had a high genetic potential and responded positively to increased nutrients supplies. Monitoring studies identified management as the major constraint to goat production in communal areas. The limitation of the study was long interval between data collection and data analysis which resulted in few recommendations being introduced on-farm. Personnel training was a major success of the programme as it helped produce two research officers for the Departement of Research and Specialist Services, a principal and lecturer of an Agricultural College, a lecturer of the University of Zimbabwe and a development researcher for a non-governmental organization.